The International Financial Crisis and Global Recession : Impact on the CEMAC Region and Policy Considerations - Milkov, Dimitre (IMF Staff Position Notes; Staff Position Note ;, 2009)
The financial sector of the Central African Economic and Monetary Community (CEMAC) has been seriously affected by the global financial crisis and resulting global recession. This note assesses the response of CEMAC governments to the global financial crisis and recession, with particular focus on the impact of current policies on each country's fiscal sustainability as well as the region's external sustainability and reserve coverage. The note then provides general policy advice to CEMAC governments as they refine their response to the global crisis.